Islamic Center Design with Islamic Architecture Design Approach - Sri Gunana Sembiring; Hastari Furqani (Talenta Publisher, 2021)
At the time of the Prophet, the mosque was a center for worship activities and economic activities, learning, socio-politics, etc. From this mosque environment, great figures in Islam were born who were not only strong in religion but also intellectually and mentally. However, the mosque has decreased in function now so that it is only a place of prayer. This phenomenon also occurs in the city of Medan, which is one of the largest cities in Indonesia, with the majority of the population being Muslim. Therefore, Medan often becomes the center of various activities, including Islamic religious activities in the area. Unfortunately, Medan does not yet have adequate facilities that can accommodate various Islamic religious activities, so it needs an activity center known as an Islamic center. The design of the Islamic center in the city of Medan solves design problems with an approach methodology ranging from literature studies, site surveys, and design concept analysis. This Islamic center applies a design concept by taking Islamic values ​​that are not indifferent to the surrounding environment so that elements of the local culture are still considered. It is hoped that this Islamic center will not only be able to become a center of activity, especially Islamic religious activities in Medan, but also an area of ​​learning about Islamic and local values ​​in its design